ANALYSIS OF THE IMPACT OF APPLYING LEAN PRODUCTION SYSTEMS ON THE EFFICIENCY OF PRODUCTION OPERATIONS IN THE IRAQI AUTOMOTIVE ASSEMBLY SECTOR (SCAI–HILLAH) IN BABYLON GOVERNORATE (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
The Iraqi automotive assembly industry is challenged with the operational challenges including low efficiency rates, high levels of waste, and little competitiveness, which demands systematic approaches to operational improvement. Using case study methodology and simulation modeling, this study attempts to look at the current situation of Kia Iraq plant, then theoretically apply lean production principles and measure expected improvements, then estimate the financial and operational impact of lean implementation and come up with practical recommendations for the Iraqi automotive assembly. The data were gathered from Kia Iraq plant (SCAI-Hillah) in Babylon Governorate, which is 124 workers, 16,800 units/year (7,200 passenger cars & 9,600 commercial vehicles), 11,513 square meters production area. Key lean production techniques such as 5S, Just-in-Time, Value Stream Mapping, and Kaizen were simulated using real factory data and it was found that realistic improvement potential through lean implementation can be shown: annual production could be increased by 12% to 18,816 units; overall efficiency could be increased from 72% to 81.2%; quality rates could be increased from 92% to 96.4%. Financial analysis shows that the potential annual benefits are $26.1 million and the implementation costs are $200,000 with a payback period of 10 months. Implementing lean production systems is a feasible option for incremental and sustainable development of Iraqi automotive assembly sector with high importance of human capacity building and developing continuous improvement culture.